Wojna sprawiedliwa a nie święta. Średniowieczne koncepcje konfliktów zbrojnych - Łuszczyńska, Małgorzata; Łuszczyński, Artur (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The aim of the article is to point out that medieval thinkers, when referring to holy wars or just righteous wars, did not seek to justify armed conflicts. The authors hereof claim that the activities of philosophers of the Middle Ages were aimed at restricting armed conflicts and focused on making the hostilities more humanitarian. Therefore, a “just war” was a war guarded by a number of preconditions which constituted a mandatory condition. The idea of a just war was rooted in the biblical tradition mainly in the New Testament and in the ancient legal thought. The medieval concept of war affected, among other things, the formation of the knight’s ethos and habits of war.
Keywords: konflikt zbrojny; święta wojna; średniowiecze